UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI PECAHAN MELALUI MEDIA KARTU PECAHAN METODE KOOPERATIF PADA SISWA KELAS II SDN 002 NONGSA TAHUN PELAJARAN 2019/2020 - Mintarsih, Mintarsih (LPPM STKIP PGRI Bandar Lampung, 2019)
This research is a Classroom Action Research. Cooperative learning is a learning strategy carried out in groups and interacting with other students. Fraction card media is a learning medium used to assist teachers in explaining the concept of simple fractions with the basic competence of comparing simple fractions. After conducting an evaluation on learning mathematics about recognizing fractions through card media, in class II the researcher experienced a failure as evidenced by the acquisition of a value that was far from the expectations of the researcher, only 10 of the 38 students could achieve the minimum completeness value, meaning only 10 students passed . In cycle I, the score was 65, out of 38 students, there were 15 students who scored above 65, so there were already 15 students who achieved the minimum completeness score, however, there are still 15 students who scored below the completeness value of learning because they still got the grade. below 65. The lowest score of the student is 40 and the highest score is 80. This success is based on the acquisition of a class average score of 77 with a grade of completeness at 93%.